Preregistration nursing students' perceived confidence in learning about patient safety in selected Kenyan universities - Nickcy N. Mbuthia; Mary M. Moleki (AOSIS, 2019)
Background: Improvement of patient safety in Kenya depends on knowledgeable nurses who are equipped with the clinical safety and sociocultural competences of patient safety. Objectives: This study assessed the theoretical and practical learning of these competences as perceived by nursing students. Method: A cross-sectional descriptive study was conducted on 178 preregistration Bachelor of Nursing students from two Kenyan universities using the Health Professional Education in Patient Safety Survey. This tool assessed the students' confidence in learning about clinical safety and the sociocultural aspects of patient safety in the classroom and clinical settings. Descriptive statistics summarised the sample and survey responses, while paired t-tests and ANOVA were used to compare responses across learning settings and year of study. Results: The students reported higher confidence about learning on the clinical aspects than on the sociocultural issues of patient safety with the lowest mean scores recorded in 'Understanding human and environmental factors' and 'Recognising, responding and disclosing adverse events'. They reported significantly higher confidence scores in the classroom setting than the clinical setting with no significant difference in reported confidence across the years of study. They were less confident in speaking up about patient safety issues in the clinical areas with 52.2% feeling that reporting a patient safety problem will result in negative repercussions. Conclusion: Nursing programmes in Kenya need to reinforce the sociocultural aspects of patient safety in the curriculum. The patient safety culture in the clinical placements sites needs to be conducive to enable, and not hinder, the acquisition of these competences.